Cross-cultural comparative analysis of student motivation and autonomy in learning: perspectives from Hong Kong and the United Kingdom - Lo, Noble Po-Kan (Frontiers in Education, 2024)
This research project examines student perspectives on independent learning in the United Kingdom and Hong Kong. Independent learning describes learning undertaken by students outside of standard institutional learning environments. Prior research has suggested that motivations to undertake independent learning and the strategies involved may differ across cultural contexts, institutions and individual learners. This research focuses on comparing the cross-cultural differences between independent learning practices and motivations to learn independently among students in Hong Kong and the United Kingdom. Taking a social constructionist approach to research, the study employs primary qualitative research consisting of interviews with 16 students in Business Studies (eight British and eight Chinese) to better establish the ways in which culture may serve as a mediator for motivation to learn independently and the strategies pursued to this end. The study's findings note key differences in the motivations to complete independent learning across either cohort, as well as distinct conceptualisations of what strategies and practices facilitate effective independent learning. This research therefore highlights significant cultural differences in the motivations, strategies and skills related to independent learning between students in the UK and Hong Kong. It also notes the potential for socioeconomic factors, institutional structures, and assessment methods, alongside culture, to contribute to these differences.